An Artistic Approach to New Testament Literature. - Chace, Sharon R. (Havertown : Lutterworth Press, 2008)
A comprehensive overview of contemporary New Testament scholarship, that explains how the Bible is and how it came to be. Coupled with notes of historical criticism, the biblical texts are described according to the formal art elements of form, line, color and texture. Other artistic terms such as perspective and focal point are used to characterize biblical passages, in order to unlock the complexity of the text. This is an introductory textbook for late high school or college students, and one that will also serve well in study groups. The art projects will be of great value for the teacher
25. The Letter to the Hebrews: Reflect on Christ the High Priest, and Continue in Faithfulness26. The Book of Revelation: Endure with Faith, and Know That in the End God Will Wipe Away Every Tear; Bibliography; Back Cover.
Print version record.
Includes bibliographical references.
Master record variable field(s) change: 072
Keywords: Bible. -- Commentaries; Bible; Bible. New Testament -- Commentaries; RELIGION -- Biblical Studies -- New Testament; RELIGION / Biblical Studies / Exegesis & Hermeneutics; Electronic books; Commentaries